Pembelajaran STEM Berbasis Engineering Design Process untuk Siswa Sekolah Alam di Kabupaten Klaten - Indah Widiastuti; Cucuk Wawan Budiyanto (FKIP Universitas Sebelas Maret, 2022)
This community service activity aims to improve STEM (Science, Technology, Engineering, and Mathematics) learning at a natural school in Klaten through engineering design. STEM is directed as integrated learning between several fields of science, especially those related to mathematics, science (physics, chemistry, biology, and environmental science), and IT (Information Technology). Learning is done by introducing several technologies that use wind energy sources. Engineering design process activities are carried out in 3 modules, namely, understanding the context of the problem, experimenting with materials and sail shapes capable of capturing wind energy, and designing windmills according to the results of previous experiments. The learning module is made by a service team with the teacher and then given to parents. Parents are expected to assist children during the implementation of activities. Students are encouraged to use STEM skills in designing windmills.